Global cartels, leniency programs and international antitrust cooperation - Jay Pil Choi; Heiko A. Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper we analyze cartel formation and self-reporting incentives when firms operate in several geographical markets and face antitrust enforcement in different jurisdictions. We are concerned with the effectiveness of leniency programs and the benefits of international antitrust cooperation between agencies. When international antitrust prosecution is uncoordinated, multi-market contact allows firms to reduce the amount of self-reporting in equilibrium and sustain cartels more effectively. We then discuss the effects of information sharing among antitrust authorities as a function of how much and which type of information is exchanged. We show that extensive information sharing might have an adverse effect on self-reporting by cartel members.
Keywords: L13; L41; D43; 330; cartel formation; multi-market contact; leniency programs; international antitrust cooperation; Konzentrationspolitik; Internationale wirtschaftspolitische Koordination; Informationsaustausch; Kartell; Straffreiheit; Ökonomischer Anreiz; Gleichgewicht; Theorie